Fungsi Bahasa dalam Acara Berasan Masyarakat Sindang Kelingi Musi Rawas - Cekman Cekman; Dedi Dedi (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this study in general is to describe the function of the rice language of the Sindang Kelingi Musi Rawas community. The data of this study are the utterances (words / languages) contained in rice activities. This study uses descriptive data in the form of written or oral words from people or observable behavior. The data source used in this research is community based activities. This research uses qualitative data analysis. Conclusion, The function of the language of rice, there are five functions, namely: 1) Personal function (only expressing joy and sadness), 2) Directive function (expressing requests and seduction), 3) Fatigue function (showing feelings of friendship), 4) Metalingual function ( explain the language itself), 5) Imaginative function (expressing the feeling that the male side faces to arrange words and respect). Keywords: Language Function, Discourse, Rice Events